Structural properties of CdS thin-films deposited by RF magnetron sputtering - Ahamed E.M.K.I.; Gupta A.K.S.; Khan M.N.I.; Matin M.A.; Amin N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Buffer layers; Cadmium sulfide; Chromium compounds; Copper compounds; Crystal structure; Crystallite size; Dislocations (crystals); II-VI semiconductors; Magnetron sputtering; Photoelectrochemical cells; Photovoltaic cells; Structural properties; Sulfur compounds; X ray diffraction; As-deposited films; Crystalline properties; Crystalline quality; Dislocation densities; rf-Magnetron sputtering; Rf-sputtering; Sputtering conditions; Thin film photovoltaic cells; Thin films